CLINICAL EVALUATION OF AFRICAN HERBAL MEDICINES - Wanbebe, Charles (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The criteria for clinical evaluation of African herbal medicines are exactly the same as those for assessing orthodox medicines (i.e. quality, safety and efficacy). The African herbal medicine may be a standardized freeze dried extract formulated into suitable dosage forms. The quality of the herbal medicine is determined by various factors which may influence the chemistry of the plant, pharmacology, toxicology and pharmaceutical formulation indicating the significance of establishing phytochemical and biological fingerprints. Generation of robust pre-clinical data on safety and efficacy based on standard pharmacological and toxicological methodologies using the principles of WHO. Good Laboratory Practice is a prerequisite to consideration of clinical trials. The design of the protocol for the clinical evaluation of herbal medicine should take cognizance of the ethnomedicinal use, clinical observational study data, national drug regulatory authority guidelines, ICH and WHO Good Clinical Practice principles. The principles indicated above were applied in the clinical evaluation of a herbal medicine called NIPRISAN for the management of Sickle Cell Disorder (SCD). Patenting of the process technology and potential therapeutic use of NIPRISAN was undertaken. In Africa where about 70% of SCD patients reside, the prevalence is about 2% (SS genes) and 25% (AS genes) among the general population while infant mortality is about 8%. Furthermore, survival rate in rural areas of SCD children by age 5 years is about 20%. Since there is no standard therapy in Africa for SCD patients, most patients use traditional herbal medicines. NIPRISAN is a standardized extract from four medicinal/food plants: Piper guineenses seed, Pterocarpus osun stem, Eugenia caryophylum fruit and Sorghum bicolor leaves. Pre-clinical data of NIPRISAN using both in vitro and in vivo methodologies indicated profound efficacy and safety profiles. SCD (Hb SS) patients confirmed by haemoglobin electrophoresis in alkaline/acid media with moderate-to-severe recurrent episodes who had experienced at least 3 painful or vaso-occlusive crises in the previous year were recruited for the study. Double-blind, placebo-controlled, randomized cross-over clinical trial of NIPRISAN was undertaken at the National Institute for Pharmaceutical Research and Development (NIPRD) clinic, Abuja between April 1997 and August 1998. Health diaries were used by all study participants. Clinical monitors (nurses) visited patients at home every week. 100 patients were recruited but 82 satisfied inclusion criteria at 3 months pre-trial period. NIPRISAN has been licensed to XECHEM Inc (an American company) and it is being commercially produced at Abuja for the global market.